Higher agricultural education and food sovereignty : pandemic and desirable and possible scenarios - Victorino Ramírez, Liberio; Ostoa Escudero, Herminia (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The objective of the article is to analyze the role of higher agricultural education (SEE) in the university context in the face of the contradictory demand of social subjects: some for adapting it to the market, others for promoting respect for human rights and food sovereignty to train professionals that guide agricultural production processes, which benefit the most vulnerable groups in the countryside and rural areas of the neoliberal capitalist system. Methodologically, it refers to futures studies, where EAS and food sovereignty as long-term options for 25, 30 or 50 years, leads us to shape traits, attend to trends, recognize uncertainties and think the impossible of total facts such as the pandemic. COVID 19, and other related socio-environmental conflicts to reinterpret the current social reality and reconstruct scenarios as possible futures in global settings, especially in a national reality such as Mexico. It is concluded that, after analyzing fifteen university institutions through global, regional, and national scenarios that thought about their time and contexts, three scenarios are synthesized for Mexico: one pessimistic; another pessimist-optimist; and an optimistic third with an orientation to respect human and social rights, and the production of safe food to achieve food sovereignty.